PERAN KELUARGA DALAM PEMBENTUKAN KARAKTER ANAK MENURUT PERSPEKTIF PENDIDIKAN MODERN - Rahma Cahyani; Mardhatillah, Rayhan; Siti Nur Syamsiyah; Muhammad Muchlish Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Family plays a fundamental role as the first and primary educational environment in shaping children's character and personality. In the context of modern education, the relationship between family and formal education institutions has become increasingly complex due to social change, globalization, and digital development. Therefore, understanding the concept of family in modern education and its role in character education becomes essential. This study aims to analyze the concept of family from the perspective of modern education and examine its contribution to character education. This research uses a qualitative approach with a literature study method by analyzing several recent academic journals related to family education and character formation. The findings indicate that the family functions as a primary educational system that shapes moral values, social attitudes, and behavioral patterns through continuous interaction, communication, and parental role modeling. The study also reveals that effective character education in the family is influenced by parenting styles, emotional closeness, and value consistency demonstrated by parents. Furthermore, the integration between family education and formal schooling is necessary to support holistic child development. However, the influence of digital media and changing social structures present new challenges for families in maintaining their educational role. Therefore, strengthening family-based education isessential to ensure the successful formation of children's character and moral values in modern society.